EVALUATION OF THE EFFICIENCY OF «GREEN» INVESTMENTS - Vytvitskyi, Yaroslav; Vytvytska, uliana (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
Abstract. The article is devoted to the development of methodological approaches to evaluating the effectiveness of "green" investments. A methodical approach has been proposed, which combines a differentiated consideration of the peculiarities of investment, obtaining environmental and economic benefits and opportunities for their use at different stages of the long life cycle of such investment projects. The life cycle of "green" investment projects has been divided into three periods - the period of investment costs (design, purchase of necessary equipment and materials, construction of the facility), payback period (rehabilitation) and after payback (primary operational) period. Environmental and economic benefits have been classified that can be obtained during the life cycle of a "green" investment project in the form of: environmental risk, which is a quantitative measure of an environmental event or accident and is defined as the product of possible damage to the environment, legal entities and individuals, and the probability of an emergency; net economic profit; direct environmental benefits of the investor; indirect environmental and economic benefits that may arise from third parties. Peculiarities of formation of ecological and economic benefits in each of the periods and possibilities of their monetization have been determined. For each period, it is envisaged to apply the relevant time factor accounting procedures (compounding, discounting), various moments of time to which the reduction of environmental and economic benefits and investment costs, discount rates and income rates that take into account the specific risks for each period. Two models for evaluating the effectiveness of "green" investments have been proposed, one of which is based on the direct identification and determination of direct and indirect environmental and economic benefits from the implementation of "green" investment projects, and the second - using adjustment factors that take into account the possibility of positive and negative externalities that may occur to third parties who are not direct participants in the projects.